Correlates of intended COVID-19 vaccine acceptance across time and countries: results from a series of cross-sectional surveys - Gabriel Recchia; Pierre Arwidson; Sander van der Linden; Carole Dufouil; Claudia R Schneider; Alexandra LJ Freeman; John R Kerr; Sarah Dryhurst; Ullrika Sahlin (BMJ Open)
Objective Describe demographical, social and psychological correlates of willingness to receive a COVID-19 vaccine.Setting Series of online surveys undertaken between March and October 2020.Participants A total of 25 separate national samples (matched to country population by age and sex) in 12 different countries were recruited through online panel providers (n=25 334).Primary outcome measures Reported willingness to receive a COVID-19 vaccination.Results Reported willingness to receive a vaccine varied widely across samples, ranging from 63% to 88%. Multivariate logistic regression analyses reveal sex (female OR=0.59, 95% CI 0.55 to 0.64), trust in medical and scientific experts (OR=1.28, 95% CI 1.22 to 1.34) and worry about the COVID-19 virus (OR=1.47, 95% CI 1.41 to 1.53) as the strongest correlates of stated vaccine acceptance considering pooled data and the most consistent correlates across countries. In a subset of UK samples, we show that these effects are robust after controlling for attitudes towards vaccination in general.Conclusions Our results indicate that the burden of trust largely rests on the shoulders of the scientific and medical community, with implications for how future COVID-19 vaccination information should be communicated to maximise uptake.